2014
DOI: 10.3341/kjo.2014.28.4.306
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Anti-vascular Endothelial Growth Factor versus Observation in Acute Central Serous Chorioretinopathy: One-year Results

Abstract: PurposeTo evaluate the efficacy of anti-vascular endothelial growth factor (VEGF) compared with observation for treating acute central serous chorioretinopathy (CSC).MethodsA retrospective study of 36 patients with acute CSC, including 21 patients treated with anti-VEGF (anti-VEGF group) and 15 patients with observation (observation group). Patients in the anti-VEGF group received a single dose of bevacizumab or ranibizumab at baseline. Best-corrected visual acuity (BCVA), central foveal thickness (CFT) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
(36 reference statements)
0
19
1
Order By: Relevance
“…[19][20][21] There is also emerging evidence that early resolution of SRF could reduce the risk of photoreceptor/ RPE degeneration and improve visual acuity. 22 However, in our study, despite the shorter resolution time in spontaneously resolved group, no difference was found between the groups in respect to the visual acuity changes during follow up. One possible reason for this nonsignificance may be the relative shorter recovery time in PDT-treated patients.…”
Section: Discussioncontrasting
confidence: 48%
“…[19][20][21] There is also emerging evidence that early resolution of SRF could reduce the risk of photoreceptor/ RPE degeneration and improve visual acuity. 22 However, in our study, despite the shorter resolution time in spontaneously resolved group, no difference was found between the groups in respect to the visual acuity changes during follow up. One possible reason for this nonsignificance may be the relative shorter recovery time in PDT-treated patients.…”
Section: Discussioncontrasting
confidence: 48%
“…The study comparing results of PDT treatment and sole 689 nm laser treatment of CSCR showed that both procedures were equally effective; however, it included cases of relatively short duration of CSCR (17-19 weeks) [ 25 ]. The efficacy of anti-VEGF treatment in chronic CSCR is disputable [ 26 29 ], with recent data failing to confirm its superiority over PDT or other therapies [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…40 Therefore, these agents have a relatively minor and controversial role in the treatment of CSC. 1,41,42 Oral treatment for CSC is an appealing idea, if it can be proven to be effective and systemically safe. Such a treatment could be the first treatment choice for patients with CSC who require intervention, to which PDT could be added later on if necessary.…”
Section: Discussionmentioning
confidence: 99%